INFLUÊNCIA DE DIFERENTES PROTOCOLOS DE TREINAMENTO FÍSICO SOBRE A FOSFORILAÇÃO DA PROTEÍNA AKT EM MÚSCULO ESQUELÉTICO E SENSIBILIDADE À INSULINA DE RATOS OBESOS - Marinho, Rodolfo; Gaspar, Rodrigo Stellzer; Pauli, Luciana Santos Souza; Cintra, Dennys Esper; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Universidade Estadual de Maringá, 2015)
ABSTRACTInvestigate the effects of different protocols of physical training (PT) on insulin sensibility (IS) and Akt phosphorylation (p-Akt) in skeletal muscle of obese rats. Animals were distributed in four groups according to the diet and physical training: Control: received standard chow (C); Sedentary obese: received high fat diet (HFD) for 12 weeks (OS); Obese Trained 1: received HFD for 12 weeks and PT without overload for 6 weeks (OT-1); Obese Trained 2: received HFD for 12 weeks and PT with overload of 5% body weight (OT-2). Insulin tolerance test was used to evaluate the IS. Western blotting was performed to evaluate p-Akt and total Akt in gastrocnemius muscle. Results: The PT with overload induced greater p-Akt, however there isn't difference in SI when compared with the training without overload. Conclusion: Differences in p-Akt not induced better responses of IS in obese rats induced by HFD.

RESUMOO Objetivo deste estudo foi investigar os efeitos de diferentes protocolos de treinamento físico (TF) sobre a sensibilidade à insulina (SI) e a fosforilação da Akt (p-Akt) no músculo de ratos obesos. Os animais foram distribuídos em quatro grupos: Controle: recebeu dieta padrão (C); Obeso sedentário: recebeu dieta hiperlipídica (DHL) por 12 semanas (OS); Obeso treinado-1: recebeu DHL por 12 semanas e TF sem sobrecarga por 6 semanas (OT-1); Obeso treinado-2: recebeu DHL por 12 semanas e TF por 6 semanas com sobrecarga de 5% da massa corporal (OT -2). O teste de tolerância à insulina foi realizado para estimar a SI. A p-Akt e Akt total no músculo gastrocnêmio foram determinadas por Western Blot. Os resultados apontam que o TF com sobrecarga induziu maior p-Akt, porém não houve diferença na SI se comparado ao TF sem sobrecarga. Como conclusão as diferenças na p-Akt não induziram respostas mais significativas de SI em ratos obesos induzidos por DHL.
INFLUENCES OF DIFFERENT PROTOCOLS OF PHYSICAL TRAINING ON THE PHOSPHORYLATION OF AKT PROTEIN IN SKELETAL MUSCLE AND INSULIN SENSITIVITY OF OBESE RATS
Keywords: Physical Training; Obesity; Insulin Signaling; Treinamento Físico; Obesidade; Sinalização da Insulina